2011
DOI: 10.1007/s10194-011-0397-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of triggers in paediatric migraine: a questionnaire study in 102 children and adolescents

Abstract: The prevalence and characterization of migraine triggers have not been rigorously studied in children and adolescents. Using a questionnaire, we retrospectively studied the prevalence of 15 predefined trigger factors in a clinic-based population. In 102 children and adolescents fulfilling the Second Edition of The International Headache Classification criteria for paediatric migraine, at least one migraine trigger was reported by the patient and/or was the parents’ interpretation in 100% of patients. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
87
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 23 publications
7
87
1
1
Order By: Relevance
“…In their study population 59% study sample was recorded with tension as the common trigger for migraine attack. More over the work of Neut et al [26] showed stress or tension and lack of sleep as most prevalent triggers for migraine. Contrarily, findings of Al-Shimmery [14] are different.…”
Section: Discussionmentioning
confidence: 99%
“…In their study population 59% study sample was recorded with tension as the common trigger for migraine attack. More over the work of Neut et al [26] showed stress or tension and lack of sleep as most prevalent triggers for migraine. Contrarily, findings of Al-Shimmery [14] are different.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the triggers most frequently reported were environmental ones, followed by stress and sleep triggers. In a study conducted by Chakravarty 2 , the triggers most frequently reported were stress followed environmental triggers, and in the study performed by Neut et al 9 were stress followed sleep deprivation. This difference, regarding our study, can be explained by ethnic, climatic, dietary and sociocultural factors.…”
Section: Discussionmentioning
confidence: 99%
“…Among the environmental triggers examined, the sun/clarity, hot weather and the smell of perfume were the most frequently cited triggers in our study. In the study conducted by Neut et al 9 , hot weather was the most frequent migraine trigger; however, the smell of perfume was not evaluated. According to the literature, sleep deprivation was the most frequently cited sleep trigger 1,2,9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations